International journal of sports science & coaching. (Brentwoood, Essex, United Kingdom Multi-Science Publishing Company, 2006)
The journal will integrate theory and practice in sports science, promote critical reflection of coaching practice, and evaluate commonly accepted beliefs about coaching effectiveness and performance enhancement. Open learning systems will be promoted in which: (a) sports science is made accessible to coaches, translating knowledge into working practice; and (b) the challenges faced by coaches are communicated to sports scientists
UP System perpetual contents: 2019
Title from journal title screen (SAGE Journals, viewed October 6, 2023)
Keywords: Coaching (Athletics) -- Periodicals; Sports sciences -- Periodicals